A role for plant science in underpinning the objective of global nutritional security?. (6th July 2018) - Martin, Cathie
Abstract: Background: The challenges of achieving global food security have become more demanding as scientists have realized that not only calorie content but also food composition and colonic microbial content impact our health and well-being, dramatically. The ways that the nutrients we consume affect our health are highly complex due to the diversity of what we eat, the varying digestibility of what we eat, the changing composition and functioning of each individual's gut microbiota, the differences in absorption and bioavailability of the nutrients we eat, the differences in responses between individuals to what they eat and the multi-fold mechanisms of action that nutrients have on our health. Perspective and Conclusions: It has been accepted for more than 50 years that diets rich in plants, particularly fruit and vegetables, protect health, and yet such diets have declined, with lower fruit and vegetable content and much more cheap, sugary, oily, processed foods, over the same period. These dietary shifts have had a marked impact on the incidence of chronic diseases: obesity, metabolic diseases, type 2 diabetes and cardiovascular diseases. Greater support for research into the ways that plant-based foods impact health will be essential for changing dietary patterns to protect health and to achieve global nutritional security.